PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI CABANG PELAYANAN DISPENDA CINERE - Imam Muhtadin; Edi Purwanto (UNIVERSITAS INDRAPRASTA PGRI, 2023)
This research is quantitative in nature, and aims to determine the effect of Employee Compensation on Employee Performance; the influence of Work Motivation on Employee Performance, and the effect of Employee Compensation and Work Motivation on Employee Performance. The population of this study were all employees of the Cinere Dispenda Service Branch, totaling 60 employees, the sample used in this study amounted to 52 employees. Validity test using bivariate Pearson correlation (Pearson product-moment). While the reliability test uses cronch alpha. The classic assumption test includes the multicollinearity test, heteroscedasticity test, and normality test. Test the hypothesis in this study using multiple regression analysis and correlation analysis of determination. The results of this study indicate that: there is no influence between Employee Compensation on Employee Performance at the Cinere Dispenda Service Branch; there is an influence between Work Motivation on Employee Performance at the Cinere Dispenda Service Branch; and Compensation and Work Motivation has a significant influence on the Performance of Cinere Dispenda Service Branch Employees.